The blue-light photoreceptor CRYPTOCHROME is expressed in a subset of circadian oscillator neurons in the Drosophila CNS. - Benito, J.; Houl, J.H.; Roman, G.W.; Hardin, P.E. (Journal of Biological Rhythms, 2008)
In the fruit fly Drosophila melanogaster, CRYPTOCHROME (CRY) functions as a photoreceptor to entrain circadian oscillators to light-dark cycles and as a transcription factor to maintain circadian oscillator function in certain peripheral tissues. Given the importance of CRY to circadian clock function, we expected this protein to be expressed in all oscillator cells, yet CRY cellular distribution and subcellular localization has not been firmly established. Here we investigate CRY spatial expression in the brain using a newly developed CRY antibody and a novel set of cry deletion mutants. We find that CRY is expressed in s-LNvs, l-LNvs, and a subset of LNds and DN1s, but not DN2s and DN3s. CRY is present in both the nucleus and the cytoplasm of these neurons, and its subcellular localization does not change over the circadian cycle. Although CRY is absent in DN2s and DN3s, cry promoter activity and/or cry mRNA accumulation can be detected in these neurons, suggesting that CRY levels are regulated posttranscriptionally. Oscillators in DN2s and DN3s entrain to environmental light-dark cycles, which implies that they are entrained indirectly by retinal photoreceptors, extraretinal photoreceptors, or other CRY-expressing cells.